Coverage and beyond: how can private governance support key elements of the Global Biodiversity Framework’s Target 3? - Lewis, Alanah Hayley; Gottlieb, Bex; Wilson, Brett; Sutton, Jack; Lessmann, Janeth; Delli, Giacomo; Dubois, Grégoire; Bingham, Heather C. (Frontiers in Conservation Science, 2023)
A vast cross-societal effort will be needed to achieve the ambition of protecting and conserving 30% of the earth’s lands and oceans by 2030, as called for in Target 3 of the Kunming-Montreal Global Biodiversity Framework. While focus is often given to the 30% coverage aspect of this target, other elements – on the location and effectiveness of protected and conserved areas – are equally important. As the implementation of Target 3 progresses, it is increasingly acknowledged that non-profit organisations, for-profit organisations, and individual landowners play a key role by choosing to manage their lands and waters to deliver conservation outcomes. However, privately protected and conserved areas lack recognition by many governments charged with reporting progress on the target. For countries and territories where these areas have been reported, we use the World Database on Protected Areas to explore their contribution towards elements of Target 3, particularly coverage, connectivity and ecological representation. In addition, we explore how privately governed ‘other effective area-based conservation measures’ contribute to Target 3 in countries and territories where they have been identified. Our results demonstrate that privately protected and conserved areas play a significant role in some countries’ efforts to meet Target 3. Since these areas are known to be under-reported, we stress the need for scaled up efforts for their recognition and documentation. This is vital not only for Target 3 tracking and implementation, but to ensure private actors receive appropriate recognition and support for their role in tackling the biodiversity and climate crises.